ANALISIS DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI - R. Aria Wira Negara (2015)
This study was conducted to examine the effect of variables General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds to Economic Growth. The population in this study are all City in the Province West of Java,Central of Java, and East of Java in 2011-2013. The sampling technique is purposive sampling method that produces a sample of 297 City in 2011-2013. The research data was obtained from the website of the Directorate General of Fiscal Balance Region and through the website of the Central Board of Statistics. Data were tested using multiple linear regression method with a significance level of 5%. The result of the test showing that there is some result that is not significant between General Allocation Fund to Economic Grwoth, Special Allocation Fund have negative significant impact to Economi Growth, and the Revenue Sharing Fund have significant effect to Economic Grwoth.